The Impact of the New Code of Ethics on the Use of Personal Telephones During Working Hours on the Formation of Ethical Behavior of Employees (Journal of Universal Excellence, 2026)
Research question (RV): "How well do employees know the Code of Ethics (EC) and House Rules (HR) and how is the use of a personal telephone (OT) during working hours?"Purpose: To determine the influence of organic organizational culture on ethical perception and productivity of employees, focusing on the use of personal phones during working hours.Method: Using a descriptive approach to review theoretical content and analyze existing literature. Conducting short interviews with employees in organization and data analysis using R-Comander and ATLAS.ti.Results: It was found that most employees know the rules regarding the use of personal phones and that the majority believe that the use of these phones reduces their productivity. The research also shows gender differences in Internet use during working hours.Organization: The findings of the research can be considered by organization when designing its human resource management strategy, which can help create a more ethical and socially responsible work environment.Society: The results of the research can also benefit the wider social environment, especially in service activities.Originality: It is important to explore the organic response of employees to new ethical guidelines, which can contribute to preventing the abuse of the ethical code in the organization.Limitations/further research: The research only focuses on small organization and does not address the impact of the new code of ethics on productivity. Future research should include larger samples and repeat studies to confirm the results.
Keywords: organization; code of ethics (EC); house rules (HR); personal telephone (OT); productivity; social responsibility